Integrating Mind-Body Practices into Nursing Education: Qualitative Insights from Students’ Learning Experiences - Nur Izgu; Zehra Gök Metin (Global Nursing Insights, 2026)
Aim: Nursing students experience considerable stress from academic and life pressures, underscoring the need for supportive strategies across both undergraduate education and lifelong professional development. Integrating mind-body-based practices into curricula may enhance well-being, resilience, and competence. This study aimed to explore nursing students’ learning experiences in the “Mind-Body-Based Practices in Nursing” course. Material and Methods: Semi-structured online interviews (October 2024–February 2025) were conducted with 17 students from a public university and analyzed using reflexive thematic analysis.Results: Participants’ mean age was 22.41 years (SD = 0.93), and most were female (88.24%). Six themes emerged: inspirations for taking the course, a genuine touch to nursing education, reflections on mind-body practices in daily life, perceptions of the course structure, one-word impressions, and perspectives from a professional standpoint.Conclusions: Findings support embedding mind-body practices into nursing curricula and continuing education programs, using experiential learning to foster holistic well-being, lifelong learning, and professional competence.Implication for nursing practice: Wider institutional partnerships and postgraduate training initiatives may facilitate the national and international scaling of mind–body education and strengthen holistic, evidence-based nursing practice.